Managing Humans Biting and Humorous Tales of a Software Engineering Manager - Lopp, Michael; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
The humor and insights in the 2nd Edition of Managing Humans are drawn from Michael Lopp's management experiences at Apple, Netscape, Symantec, and Borland, among others. This book is full of stories based on companies in the Silicon Valley where people have been known to yell at each other and occasionally throw chairs. It is a place full of dysfunctional bright people who are in an incredible hurry to find the next big thing so they can strike it rich and then do it all over again. Among these people are managers, a strange breed of people who, through a mystical organizational ritual, have been given power over the future and bank accounts of many others. Whether you're an aspiring manager, a current manager, or just wondering what the heck a manager does all day, there is a story in this book that will speak to you$1 (Band help you survive and prosper amongst the general craziness. Lopp's straight-from-the-hip style is unlike any other writer on management. He pulls no punches and tells stories he probably shouldn't. But they are massively instructive and cut to the heart of the matter whether it's dealing with your boss, handling a slacker, hiring top guns, or seeing a knotty project through to completion. This second editions expands on the management essentials. It will explain why we hate meetings, but must have them, it carefully documents the right way to have a 1-on-1, and it documents the perils of not listening to your team. Writing code is easy. Managing humans is not. You need a book to help you do it, and this is it.s
Keywords: Economics; Economics/Management Science; Business/Management Science, general